Salmonella Typhimurium DT193 and DT99 are present in great and blue tits in Flanders, Belgium - R. Boonyarittichaikij (2018)
© 2017 Boonyarittichaikij et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Endemic infections with the common avian pathogen Salmonella enterica subspecies enterica serovar Typhimurium (Salmonella Typhimurium) may incur a significant cost on the host population. In this study, we determined the potential of endemic Salmonella infections to reduce the reproductive success of blue (Cyanistes caeruleus) and great (Parus major) tits by correlating eggshell infection with reproductive parameters. The fifth egg of each clutch was collected from nest boxes in 19 deciduous forest fragments. Out of the 101 sampled eggs, 7 Salmonella Typhimurium isolates were recovered. The low bacterial prevalence was reflected by a similarly low serological prevalence in the fledglings. In this study with a relatively small sample size, presence of Salmonella did not affect reproductive parameters (egg volume, clutch size, number of nestlings and number of fledglings), nor the health status of the fledglings. However, in order to clarify the impact on health and reproduction a larger number of samples have to be analyzed. Phage typing showed that the isolates belonged to the definitive phage types (DT) 193 and 99, and multi-locus variable number tandem repeat analysis (MLVA) demonstrated a high similarity among the tit isolates, but distinction to human isolates. These findings suggest the presence of passerine-adapted Salmonella strains in free-ranging tit populations with host pathogen co-existence.